The Fibrinolytic Potential of the Normal Primate following the Generation of Thrombin In Vivo - Giles, Alan R; Nesheim, Michael E; Herring, Steven W; Hoogendoorn, Hugh; Stump, David C; Heldebrant, Charles M (Thrombosis and Haemostasis, 1990)
Parameters of the fibrinolytic system were studied in a primate model where the generation of thrombin was promoted in vivo. The procoagulant stimulus used was a combination of human factor Xa in combination with phosphatidylcholine/phos-phatidylserine lipid vesicles (PCPS) as the source of coagulant active phospholipid. The dosage of each component was formulated to provide a gradation of thrombin generating potential assessed prior to in vivo study in an in vitro clotting assay. These ranged from 25.25 - 36.60 pMole/kg (factor Xa) and 18.85 - 56.30 nMole/kg (PCPS). In each case, the ratio of the dose of factor Xa/PCPS was maintained at 0.65 (pMole factor Xa/ nMole PCPS). Individual dosage combinations producing recalcification clotting times in vitro of 15, 20, 25 and 30 s were used in detailed in vivo studies. Previous studies in dogs had confirmed the thrombin generating potential of factor Xa/PCPS infusions and demonstrated an associated activation ot protein C and increased fibrinolytic activity. This has now been extensively characterized in the chimpanzee as follows: 10 min after the infusion of the highest dose (36.6 pMole factor Xa/56.3 nMole PCPS kg bodyweight), the level of circulating t-PA had risen to 900 ng/ml (antigen), 885 IU/ml (functional). Dosage was observed with the lowest dose of 12.25 pMole factor Xa and 18.85 nMole PCPS being associated with relatively minor increases in circulating t-PA activity. There were no changes in u-PA at any dosage during the full time course of the experimental period (90 min). Plasminogen activation was also apparent with alpha-2 antiplasmin levels falling to 30 - 40% of pre-infusion levels at the highest dosages. There was also a significant consumption of fibrinogen and evidence of active fibrinolysis manifested by major increases in the levels of FDP, D-dimer and B-beta 1-42. The data strongly suggested that this was predominantly fibrinolysis rather than fibrinogenolysis and that the fibrinolytic response observed resulted from a major release of t-PA from available stores consequent to thrombin generation and presumably subsequent fibrin generation. These data illustrate the enormous fibrinolytic potential of the intact normal primate and may provide a model for study of the mechanism(s) by which the regulation of t-PA availability can be up- or down-regulated in health and disease.